Migratory Sheep Farming Practices in Cauvery Delta Zone in Tamil Nadu - Kannadhasan, MS; Chander, Mahesh; Bardhan, D (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Migratory sheep, due to its movement, poses threat of spreading diseases among small ruminants. Considering this, the study was carried  out to identify the focus area of extension intervention among the migratory sheep farmers to disseminate scientifically recommended  practices which minimize disease risk and enhance flock health. The study was conducted following ex post fact research design at  Venganur village, Cuddalore district, Tamil Nadu. Using a semi-structured interview schedule, data were personally collected from 30  migratory sheep farmers who were selected purposively. The findings were subjected to focussed group interview involving seven  farmers. The results envisaged a wider difference among the farmers from 100 per cent non-adoption of balanced ration to 100.00 per  cent adoption of deworming. Therefore, extension interventions need to be intensified to educate the farmers on technologies which  help in disease prevention and control.
Keywords: Flock health; Migratory sheep farming; Recommended farming practices